2004
DOI: 10.1177/026010600401800103
|View full text |Cite
|
Sign up to set email alerts
|

Change in the Ascorbic Acid, Total Phenol and Antioxidant Activity of Sun-dried Commonly Consumed Green Leafy Vegetables in Nigeria

Abstract: Sun-drying of green leafy vegetables is popularly practised in many homes in Nigeria, as a way of preserving green leafy vegetables for future use. This project sought to investigate the effect of this method of preservation of vegetables on the antioxidant phytoconstituent (Vitamin C and Total phenol) and activity (reducing property and free radical scavenging ability) of some commonly consumed green leafy vegetables in Nigeria namely Structium sparejanophora (Ewuro-odo), Amarantus cruentus (Atetedaye), Telfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
96
3
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(113 citation statements)
references
References 13 publications
11
96
3
3
Order By: Relevance
“…The result revealed that unprocessed T. occidentalis leaf had a significantly (P<0.05) higher total phenol (13.0 mg/100g) and flavonoid (7.3 [10] reported for some tropical green leafy vegetables (1 -3 mg/g). The difference in phenolic value is as a result of the extraction medium used in the study.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The result revealed that unprocessed T. occidentalis leaf had a significantly (P<0.05) higher total phenol (13.0 mg/100g) and flavonoid (7.3 [10] reported for some tropical green leafy vegetables (1 -3 mg/g). The difference in phenolic value is as a result of the extraction medium used in the study.…”
Section: Discussionmentioning
confidence: 88%
“…However, numerous studies have conclusively shown that the majority of the antioxidant activity may be from compound such as flavonoids, isoflavone, flavones, anthocyanin, catechin and isocatechin, rather than vitamins C, E and 毬-carotene [8] . Several green leafy vegetables with high phenolic contents abound in tropical Africa, they are utilized either as condiments or spices in human diets [9] ; these vegetables could be harvested at all stages in the process of growth, and could be fed upon in fresh, processed, or semiprocessed forms [10,11] . They are very rich sources of 毬-carotene, ascorbic acid, minerals and dietary fiber [12] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations